THE EFFECTS OF VARYING CO2 CONCENTRATION ON LIPID COMPOSITION AND CARBON ISOTOPE FRACTIONATION IN EMILIANIA HUXLEYI - Riebesell U.; Revill A.T.; Holdsworth D.G.; Volkman J.K. (My University, 2000)
We have measured the stable carbon isotopic composition of bulk organic matter (POC), alkenones, sterols, fatty acids, and phytol in the coccolithophorid Emiliania huxleyi grown in dilute batch cultures over a wide range of CO2 concentrations (1.1–53.5 μmol L−1). The carbon isotope fractionation of POC (εPOC) varied by ca. 7‰ and was positively correlated with aqueous CO2 concentration [CO2aq]. While this result confirms general trends observed for the same alga grown in nitrogen-limited chemostat cultures, considerable differences were obtained in absolute values of εPOC and in the slope of the relationship of εPOC with growth rate and [CO2aq]. Also, a significantly greater offset was obtained between the δ13C of alkenones and bulk organic matter in this study compared with previous work (5.4, cf. 3.8‰). This suggests that the magnitude of the isotope offset may depend on growth conditions. Relative to POC, individual fatty acids were depleted in 13C by 2.3‰ to 4.1‰, phytol was depleted in 13C by 1.9‰, and the major sterol 24-methylcholesta-5,22E-dien-3β-ol was depleted in 13C by 8.5‰. This large spread of δ13C values for different lipid classes in the same alga indicates the need for caution in organic geochemical studies when assigning different sources to lipids that might have δ13C values differing by just a few ‰. Increases in [CO2aq] led to dramatic increases in the alkenone contents per cell and as a proportion of organic carbon, but there was no systematic effect on values of U37k′ used for reconstructions of paleo sea surface temperature.